Young women's anterior cruciate ligament injuries: An expanded model and prevention paradigm - Elliot, D. L.; Goldberg, L.; Kuehl, K. S. (Sports Medicine, 2010)
Anterior cruciate ligament (ACL) injuries among young female athletes occur at rates three- to eight-times greater than in male competitors and, in general, females experience more sports injuries than males, when balanced for activity and playing time. ACL injuries are a particular concern, as they result in immediate morbidity, high economic costs and may have long-term adverse effects. While several closely monitored ACL injury preventive programmes have been effective, those efforts have not been uniformly protective nor have they achieved widespread use. To date, ACL injury prevention has focused on neuromuscular and anatomical factors without including issues relating more broadly to the athlete. Coincident with greater female sport participation are other influences that may heighten their injury risk. We review those factors, including early single sport specialization, unhealthy dietary behaviours, chronic sleep deprivation and higher levels of fatigue, substance use and abuse, and psychological issues. We augment existing models of ACL injury with these additional dimensions. The proposed expanded injury model has implications for designing injury prevention programmes. High school athletic teams are natural settings for bonded youth and influential coaches to promote healthy lifestyles, as decisions that result in better athletes also promote healthy lifestyles. As an example of how sport teams could be vehicles to address an expanded injury model, we present an existing evidenced-based sport team-centered health promotion and harm reduction programme for female athletes. Widening the lens on factors influencing ACL injury expands the prevention paradigm to combine existing training with activities to promote psychological well-being and a healthy lifestyle. If developed and shown to be effective, those programmes might better reduce injuries and, in addition, provide life skills that would benefit young female athletes both on and off the playing field.